Influence of Luminal Communication on Aortic Enlargement after Hemiarch Replacement for Acute Type A Aortic Dissection - Uchino, Gaku; Yoshida, Takeshi; Kakii, Bunpachi; Furui, Masato (The Thoracic and Cardiovascular Surgeon, 2020)
Background Aortic enlargement after hemiarch replacement (HAR) for acute type A aortic dissection (AAAD) is a serious problem. We reviewed our experience and analyzed the risk factors for aortic enlargement.Methods During April 2005 to December 2017, 364 patients underwent HAR for AAAD. Seventy-three patients fulfilled the inclusion criteria. We analyzed the change in aortic diameter, aortic growth rate, and major adverse aortic events (MAAEs) and their association with luminal communication of the aortic arch.Results Anastomotic communication, supra-aortic communication (SAC), and distal aortic communication were found in 34 (46.6%), 28 (38.4%), and 20 (27.4%) patients, respectively. The aortic growth rate was high because of the presence of SAC, distal aortic communication, and the number of coexisting aortic communication. Univariate analysis showed that the presence of SAC and an initial aortic diameter > 35 mm at 20 mm distal to the left subclavian artery and at the pulmonary artery bifurcation (PAB) were risk factors for MAAEs. Multivariate analysis showed that SAC and an initial aortic diameter > 35 mm at the PAB were independent risk factors for MAAEs.Conclusion SAC, distal aortic communication, and the number of coexisting aortic communication are significant risk factors for aortic enlargement after HAR for AAAD. SAC and an initial aortic diameter > 35 mm at the PAB are independent risk factors for MAAEs after this procedure.
Keywords: hemiarch replacement; acute type A aortic dissection; aortic growth; aortic enlargement; supra-aortic communication